2015
DOI: 10.1111/apa.13027
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity decreased by a quarter in the 11‐ to 12‐year‐old Swedish boys between 2000 and 2013 but was stable in girls: a smartphone effect?

Abstract: Time trends in physical activity differed between boys and girls. Second-grade boys and fifth-grade girls were stable throughout, whereas second-grade girls increased from 2000 to 2006 before stabilising. Fifth-grade boys showed a significant 24% reduction from 2000 to 2013. Changes in recess and leisure time habits, such as smartphone use, may have influenced the result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 27 publications
3
22
2
Order By: Relevance
“…Moreover, the proportion of those participants who achieved the recommended SPD was similar in both sexes in both study years. These findings were consistent with other data from Sweden, which showed that mean weekday SPD in eightyear-old children was stable from 2000 to 2006 and increased from 2000 to 2013 (15,16). Furthermore, the total number of steps recorded among eight-year-olds in 2017, namely 13 565 in girls and 17 062 SPD in boys, were relatively high from an international perspective (24).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Moreover, the proportion of those participants who achieved the recommended SPD was similar in both sexes in both study years. These findings were consistent with other data from Sweden, which showed that mean weekday SPD in eightyear-old children was stable from 2000 to 2006 and increased from 2000 to 2013 (15,16). Furthermore, the total number of steps recorded among eight-year-olds in 2017, namely 13 565 in girls and 17 062 SPD in boys, were relatively high from an international perspective (24).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, school children and adolescents living contemporary lifestyles seem to accumulate fewer SPD than ones living in traditional communities, such as farming communities with no modern technology. Compared to other Sweden studies that showed that pedometer-determined mean weekday SPD increased from 2000 to 2006 and remained stable from 2000 to 2008 (15,16), our results suggest that such positive figures have been somewhat halted and even reversed. With the exception of the results for eight-year-olds, which were stable for girls and increased for boys, we found that both mean SPD and the proportion reaching the published SPD recommendation were lower in 2017 than 2000.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Thus encouraging physical activity in children with JIA is likely to have a beneficial effect. In an age where exercise in children is falling [19], the paediatric rheumatology multidisciplinary team should explore new interactive technologies to increase physical activity adherence.…”
Section: Encouraging Physical Activitymentioning
confidence: 99%